A companion to Ostrogothic Italy
1 online resource.
Keywords: A Companion to Ostrogothic Italy is a concise yet comprehensive cutting edge survey of the rise and fall of Italy’s first barbarian kingdom, the Ostrogothic state (ca. 489-554 CE). The volume’s 18 essays provide readers with probing syntheses of recent scholarship on key topics, from the Ostrogothic army and administration to religious diversity and ecclesiastical development, ethnicity, cultural achievements, urbanism, and the rural economy. Significantly, the volume also presents innovative studies of hitherto under-examined topics, including the Ostrogothic provinces beyond the Italian lands, gender and the Ostrogothic court, and Ostrogothic Italy’s environmental history. Featuring work by an international panel of scholars, the volume is designed for both new students and specialists in the field. Contributors are Jonathan Arnold, Shane Bjornlie, Samuel Cohen, Kate Cooper, Deborah Deliyannis, Cam Grey, Guy Halsall, Gerda Heydemann, Mark Johnson, Sean Lafferty, Natalia Lozovsky, Federico Marazzi, Christine Radtki, Kristina Sessa, Paolo Squatriti, Brian Swain, and Rita Lizzi Testa.